A kind of waterborne polyurethane fiber and its preparation method and application

Through the homogeneous dispersion of aqueous polyurethane, sodium alginate and liquid metal and wet spinning process, highly conductive and stable core sheath structure elastic conductive fibers were prepared, which solved the decline in conductivity of existing materials under high tensile conditions. The problem of achieving high-performance fibers suitable for flexible electronic products.

CN116288798BActive Publication Date: 2025-02-18DONGHUA UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310282950.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-02-18
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

The current polymer-based conductive materials have sharply decreased under high tensile conditions, making it difficult to prepare highly conductive and electrically stable elastic conductive fibers.

Method used

By using the preparation method of aqueous polyurethane fiber, the aqueous polyurethane solution is mixed with sodium alginate and liquid metal, homogeneously dispersed, and the supernatant is removed after standing to obtain fibers. The method includes wet spinning and coaxial wet spinning processes, and the design of the elastic conductive fibers of the LM-WPU core sheath structure.

Benefits of technology

It achieves elastic conductive fibers with high conductivity, conductivity stability and good mechanical strength, with sensitive strain sensing functions and friction power-on ability, and is suitable for flexible electronic sensing and friction power fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116288798B_ABST
    Figure CN116288798B_ABST
Patent Text Reader

Abstract

The present invention relates to a waterborne polyurethane fiber and a preparation method and application thereof. The preparation method realizes wet spinning of waterborne polyurethane and realizes wet spinning preparation of elastic conductive fiber without organic solvent. The present invention is a green wet spinning process without organic solvent, which simply and efficiently prepares a core-sheath structure elastic conductive fiber with high conductivity and stable conductivity. It has wide application potential in the fields of flexible electronic sensing and triboelectricity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fibers, and particularly relates to a waterborne polyurethane fiber and a preparation method and application thereof. Background Art

[0002] Flexible wearables are an important development trend of future electronic products, and elastic conductive fibers are important basic materials for flexible wearable electronic products. The key issue of elastic conductive fibers is to prepare elastic conductive fibers with high conductivity and stable conductivity. At the same time, how to obtain elastic conductive fibers with excellent performance with green and simple preparation methods is still a challenging task, which is of great significance to the development of flexible wearable electronic products.

[0003] Existing polymer-based conductive materials often face the contradiction between "elasticity" and "conductivity": under high tensile conditions, conductive composite materials based on polymer matrices will suffer from a sharp drop in conductivity due to the separation of conductive fillers. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a waterborne polyurethane fiber and a preparation method and application thereof.

[0005] A method for preparing a waterborne polyurethane fiber of the present invention comprises:

[0006] (1) stirring and mixing an aqueous polyurethane solution and sodium alginate SA, and degassing to obtain a spinning solution A;

[0007] (2) mixing the aqueous polyurethane solution and the liquid metal, uniformly dispersing them, allowing them to stand, and removing the supernatant to obtain a slurry;

[0008] (3) directly wet spinning the spinning solution A of step (1) to obtain fibers;

[0009] Or the spinning solution A in step (1) is used as the sheath spinning solution, and the LM slurry in step (2) is used as the core slurry,

[0010] Fibers were obtained by coaxial wet spinning.

[0011] The preferred method of the above preparation method is as follows:

[0012] The aqueous polyurethane solution in step (1) is a carboxylic acid type aqueous polyurethane.

[0013] The waterborne polyurethane is prepared by the following method:

[0014] The polytetrahydrofuran ether diol PTMEG is vacuum-dehydrated, isophorone diisocyanate IPDI and dibutyltin dilaurate DBTDL are added, and the mixture is reacted at 60-90°C for 0.5-4h, 2,2-dihydroxymethylbutyric acid DMBA solution is added, a solvent (tetrahydrofuran THF) is added, and the mixture is reacted at 40-80°C for 10-30h, triethylamine TEA is added, and the mixture is reacted for 0.2-2h, deionized water is added, and the mixture is stirred at high speed (500-5000rpm) for 1-24h to obtain a polyurethane dispersion solution, and the solvent is removed by rotary evaporation to obtain a waterborne polyurethane (WPU) solution.

[0015] The mass ratio of the PTMEG, IPDI, DBTDL, DMBA and TEA is (18-14:10-6:0.04-0.02:6-2:5-1).

[0016] The solid content of the aqueous polyurethane solution in step (1) is 5-50% (solid content is the mass fraction of polyurethane in the aqueous polyurethane solution); the sodium alginate SA is 0.5-3% of the mass percentage of the aqueous polyurethane (that is, SA is 0.5-3% of the mass of polyurethane in the aqueous polyurethane).

[0017] The solid content of the aqueous polyurethane solution in step (2) is 5-50%; the liquid metal is a gallium-indium alloy or a gallium-indium-tin alloy; and the mass ratio of the aqueous polyurethane to the liquid metal LM is 10:1-1:10.

[0018] The homogenizing and dispersing in step (2) is performed at a speed of 2000-20000 r / min; and the standing time is 3-10 min.

[0019] In the step (3), the wet spinning needle in the wet spinning is 10-18G, the extrusion speed is 2-200ml / h, the winding speed is 1-50r / min, and the coagulation bath is one or more of 1-10wt% calcium chloride, copper chloride, magnesium chloride, and zinc chloride solutions.

[0020] In the step (3), the coaxial wet spinning coaxial spinning needle is one of 18G / 14G, 19G / 15G, 22G / 17G, 25G / 18G, and 30G / 21G, the outer layer spinning speed is 2-200ml / h, the inner layer spinning speed is 1-200ml / h, and the coagulation bath is a 1-10%wt calcium chloride solution.

[0021] The invention discloses a waterborne polyurethane fiber prepared by the method, wherein the fiber is a waterborne polyurethane fiber with a hollow structure or an elastic conductive fiber with a core-sheath structure.

[0022] An application of the waterborne polyurethane fiber of the present invention in electronic devices, such as wearable electronic devices.

[0023] The present invention utilizes the high-speed stirring of a homogenizer to efficiently micronize the LM dispersed in the WPU. At the same time, the oxide layer on the surface of the LM particles can produce ion adsorption with the carboxyl groups on the WPU segments, thereby achieving the coating of the LM particles by the WPU layer. The WPU coating layer can make the LM evenly and stably dispersed in the aqueous solution, and at the same time reduce the surface tension of the LM, so that the LM can be continuously and evenly extruded by microinjection. The present invention not only provides a preparation method for a conductive filler in an LM aqueous solution system, but also further combines the WPU wet spinning process to design a LM-WPU core-sheath structure elastic conductive fiber wet process. With the continuous extrusion of the LM conductive slurry, the self-stretching spinning of the elastic conductive fiber can be achieved. No organic solvent is used in the fiber preparation process, which is a green, simple and efficient wet spinning method. At the same time, the prepared fiber size is at the micron level, with an obvious core-sheath structure and good flexibility.

[0024] Beneficial Effects

[0025] The addition of SA in the present invention can effectively increase the spinnability of the WPU solution in the wet spinning process, making the fiber smoother and more uniform. Based on the wet spinning process, it is found that hollow fibers with different wall thicknesses can be obtained by soaking the fiber in the coagulation bath for different times.

[0026] The present invention is based on the chelation effect between the carboxyl group of carboxylic acid-type WPU and the gallium ion of LM oxide layer, and can prepare a uniformly dispersed LM dispersion system in an aqueous solution that can be used for microinjection extrusion. At the same time, combined with the WPU wet spinning process, the coaxial wet spinning process is successfully implemented to prepare the core-sheath structure conductive fiber. The prepared core-sheath structure elastic conductive fiber has a distinct core-sheath structure, a fiber size of 600-800 microns, and the ability to be knitted and woven. At the same time, the elastic conductive fiber has high conductivity, good mechanical strength and elongation at break, and has a stable resistance change under large deformation. The prepared elastic conductive fiber has a sensitive strain sensing function and friction electrification ability through a weaving treatment method.

[0027] The present invention discloses a green organic solvent-free wet spinning process, which simply and efficiently prepares a highly conductive and stable conductive core-sheath elastic conductive fiber, which has a wide range of application potentials in the fields of flexible electronic sensing and triboelectricity. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Design for wet spinning of waterborne polyurethane; (a) preparation of waterborne polyurethane spinning solution modified by sodium alginate (b) schematic diagram of waterborne polyurethane wet spinning process;

[0029] Figure 2The coaxial wet spinning process design for core-sheath conductive fibers; wherein (a) sheath spinning solution preparation (b) core spinning solution preparation (c) coaxial wet spinning process schematic diagram;

[0030] Figure 3 The effect of sodium alginate on aqueous polyurethane solution; (a) the effect of sodium alginate content on solution viscosity, (b) the effect of sodium alginate content on solution particle size;

[0031] Figure 4 (a) The effect of sodium alginate on waterborne polyurethane spinning; (b) The effect of immersion time on the hollow wall thickness of polyurethane elastomer fibers;

[0032] Figure 5 This is a study of liquid metal dispersed in waterborne polyurethane. (a) Comparison of liquid metal dispersion in water and waterborne polyurethane, (b) Characterization of liquid metal particle size, (c) Characterization of liquid metal structure, (d) Infrared characterization of liquid metal, (e) Characterization of contact angles of pure liquid metal and liquid metal particles dispersed in waterborne polyurethane, (f) Comparison of spinning paths of pure liquid metal, water-dispersed liquid metal, and waterborne polyurethane-dispersed liquid metal;

[0033] Figure 6 The spinning process and structure characterization of core-sheath conductive fibers. (a) Schematic diagram of the coaxial wet spinning process, (b) conductive fiber collection and winding diagram, (c) fiber surface and cross-section characterization, cross-section element distribution characterization, (d) size and flexibility characterization;

[0034] Figure 7 Characterization of conductive fiber performance. (a) Characterization of fiber circuit activation (b) Characterization of fiber conductivity (c) Characterization of fiber mechanical properties (d) Characterization of fiber resistance change rate under tensile deformation (e) Characterization of fiber resistance change rate after 200% tensile cycle (f) Characterization of fiber resistance change rate under bending deformation. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0036] Table 1 Experimental drugs

[0037]

[0038] Related tests and characterizations:

[0039] Particle size test of WPU-SA solution: The particle size of WPU-SA solution was characterized by using a nanoparticle size and potential analyzer. WPU-SA solutions with SA contents of 0, 0.5%, 1%, 1.5%, 2%, and 2.5% were diluted tenfold and then the particle size was tested. Viscosity test of WPU-SA solution: The viscosity of WPU-SA solution was characterized by using an Anton Paar rotational rheometer. WPU-SA solutions with SA contents of 0, 0.5%, 1%, 1.5%, 2%, and 2.5% were tested for the relationship between viscosity and shear rate.

[0040] Calculation of hollow fiber wall thickness: Observe the cross-sectional morphology of the prepared hollow fiber under an ultra-depth-of-field microscope, and count the fiber wall thickness after immersion for 1 min, 2 min, 4 min, 6 min, 8 min, and 10 min, respectively. Take the wall thickness of at least three fibers in each group and take the average value.

[0041] Infrared characterization: Tested using a Fourier transform infrared spectrometer equipped with an attenuated total reflectance accessory, wave number scanning range: 500-4000cm -1 , scan times: 32.

[0042] LM particle appearance characterization: Use an optical microscope at low and high magnifications to observe the existence of LM particles dispersed in deionized water and WPU. Use an ultra-depth microscope and a scanning electron microscope to characterize the size of LM particles. Spinning path characterization: Use pure LM, LM particles dispersed in deionized water, and LM particles dispersed in WPU as conductive slurries, set the injection pump extrusion speed to 10ml / h, place a piece of white paper under the needle, and pull it at a constant speed to simulate the spinning path.

[0043] LM contact angle characterization: Pure LM and WPU dispersed LM conductive slurry were dropped on the polyurethane film respectively, and the contact angle was measured using a contact angle meter. The film was stretched 50% and maintained, and the contact angle was measured again.

[0044] Fiber interface surface characterization: The cross section of the core-sheath fiber was obtained by brittle fracture in liquid nitrogen, and the fiber surface and interface samples were sprayed with gold. The field emission electron microscope (SEM) and the corresponding EDS images were used to characterize the fiber surface and cross-sectional characteristics, and the distribution of carbon (C), calcium (Ca), gallium (Ga), and indium (In) elements in the fiber cross section was characterized.

[0045] Fiber appearance characterization: Under the same magnification, the fiber size is observed using an optical microscope, and the fibers are knotted and passed through a needle, and then characterized and observed using an optical microscope.

[0046] Fiber stretching activation test characterization: Use an optical microscope to observe the surface characteristics of the unactivated elastic conductive fiber, then stretch the fiber by 20% and 100%, maintain the stretching, and observe the fiber surface characteristics; at the same time, use a universal testing machine to stretch the fiber 100%, cycle 5 times, and use a multimeter to record the change in fiber resistance during the first stretch.

[0047] Fiber cyclic incremental resistance change test: connect the two ends of the unactivated elastic conductive fiber to copper electrodes, use a universal testing machine to perform 100% cyclic incremental stretching each time, and use a multimeter to detect the real-time changes of the elastic conductive fiber.

[0048] Conductivity test of elastic conductive fiber: Take about 4cm of elastic conductive fiber, connect copper electrodes at both ends, and then connect to the resistance measuring device. Clamp both ends on the fixture of the electronic universal testing machine, and stretch the elastic fiber 5 times with 100% strain cycle. Release the stretching and record the resistance of the elastic conductive fiber in the stable state. Measure the fiber length L and fiber diameter D, calculate the fiber cross-sectional area S based on the fiber diameter, and calculate the conductivity as σ=L / (S×R)

[0049] Fiber tensile strength test, tensile strain and resistance change relationship test: The activated elastic conductive fiber is subjected to a single tensile test using a universal testing machine, and a multimeter is used to detect the resistance change at the same time.

[0050] Fiber stretching cycle resistance change test: The activated elastic conductive fiber is subjected to a 200% stretching cycle test using a universal testing machine, and the resistance change is detected using a multimeter.

[0051] Fiber bending resistance change test: The activated elastic conductive fiber is compressed and bent using a universal testing machine, and a multimeter is used to record the resistance change of the fiber at different degrees of compression and bending.

[0052] Example 1

[0053] Synthesis of Carboxylic Acid-Based Waterborne Polyurethane

[0054] Take 10.000g of polytetrahydrofuran ether diol (PTMEG), add it to a 500ml three-necked flask, and remove water under vacuum at 110℃ for 2h. Add 4.446g of isophorone diisocyanate (IPDI) and 0.01g of dibutyltin dilaurate (DBTDL), and react at 80℃ for 2h. Add 1ml of 1.342g / ml tetrahydrofuran solution of 2,2-dihydroxymethylbutyric acid (DMBA), add 9ml of tetrahydrofuran (THF), react at 60℃ for 22h, add 1.01g of triethylamine (TEA), and react for 0.5h. Add 60ml of deionized water, stir at high speed (2000rpm) for 2h to obtain a polyurethane dispersion solution. Remove tetrahydrofuran by rotary evaporation to obtain a waterborne polyurethane (WPU) solution with a solid content of 25%.

[0055] Preparation of waterborne polyurethane-sodium alginate composite solution

[0056] Take 10g of synthesized WPU respectively, weigh SA according to the content of SA in polyurethane of 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, respectively, and then add it to WPU respectively, stir and mix for 2h, and obtain WPU-SA solutions with different SA contents.

[0057] Take 10g WPU, add 0.025g SA to prepare spinning solution, and let it stand for degassing. Prepare 1000ml 2wt% CaCl2 solution as coagulation bath. Use syringe and injection pump device to select 14G (diameter 1.69mm) uniaxial spinning needle, extrude at a constant speed of 100ml / h, stretch and wind the extruded fiber at 5r / min, and quickly form it after entering the coagulation bath.

[0058] like Figure 3 As shown in (a), the relationship between the viscosity of solutions with different SA contents and the shear rate was obtained by using the Anton Paar rotational rheometer. 0 represents a pure WPU solution with a solid content of 25%. It can be seen that the viscosity of the WPU solution with a solid content of 25% is about 37Pa·s at a frequency of 1Hz. When the SA mass fraction is 1%, the viscosity of the solution increases to about 58Pa·s. When the SA content is 2%, the viscosity will increase to about 435Pa·s. It shows that as the SA mass fraction increases, the viscosity of the WPU-SA dispersion will increase. This is because the viscosity of SA itself is very large, which leads to an increase in the overall viscosity of the dispersion.

[0059] The relationship between WPU particle size and SA content was investigated using a nanoparticle size and potential analyzer. Figure 3 (b) Characterization of particle size of WPU with different SA contents. It can be found that the particle size of pure WPU is concentrated around 40nm. With the addition of SA, the particle size gradually increases, and the particle size distribution becomes wider. Further, it can be found that as the SA content increases in the range of 0-2.5%, it will first increase and then decrease with the increase of SA content. The area with the largest particle size is around 1.5%, which is around 75nm.

[0060] like Figure 4 As shown in (a), from the surface morphology of the fiber obtained by spinning pure WPU, it can be seen that the surface of the elastomer fiber formed by the ion cross-linking spinning and stretching of the WPU chain segments is rough and uneven, and the poor stretchability and mechanical strength are not conducive to the preparation of wet-spun fibers of WPU. After adding appropriate SA, the double network structure elastomer composed of SA-WPU can obtain polyurethane elastic fibers with uniform and smooth surfaces after wet spinning and stretching, as well as fiber strength that can support stretching and collection spinning.

[0061] Example 2

[0062] Preparation of waterborne polyurethane-sodium alginate wet spinning fibers

[0063] Take 10g WPU (WPU preparation is the same as in Example 1), add 0.025g SA to prepare spinning solution, and let it stand for degassing. Prepare 1000ml 2wt% CaCl2 solution as coagulation bath. Use syringe and injection pump device to extrude at a constant speed of 100ml / h, stretch and wind the extruded fiber at 5r / min, and quickly shape it after entering the coagulation bath. Take out the fibers after soaking for different time, and take them out after soaking in deionized water for 24h.

[0064] By controlling the immersion time of wet-spun fibers in the coagulation bath CaCl2, hollow elastomeric fibers with different wall thicknesses can be obtained, such as Figure 4 As shown in (b), the fiber has different wall thicknesses when immersed in the coagulation bath for 20s, 2min, 5min, 20min, and 30min. The fiber can obtain uniform hollow fibers within the 0-10min immersion time. As the immersion time increases, the hollow structure inside the fiber gradually shows a hierarchical structure. Figure 4 (b) The relationship between the wall thickness of the hollow structure fiber and time at different immersion times was obtained. As time increases, the average wall thickness of the fiber increases and the fiber wall thickness becomes more uniform.

[0065] Example 3

[0066] Spinning solution preparation

[0067] Preparation of sheath spinning solution: Take 10 ml of WPU with 25% solid content (prepared as in Example 1), add SA powder with 1% polyurethane content, stir for 1 hour to fully dissolve SA, obtain uniform spinning solution, and then perform low-temperature degassing treatment.

[0068] Preparation of core conductive slurry: Take 20ml WPU with a solid content of 25%, weigh 5g LM and add it to WPU, put it in a homogenizer, 10000rpm, disperse it for 30min, let it stand for 5min, remove the upper clear liquid, and obtain LM dispersed particle conductive slurry. (LM is dispersed in deionized water in the same way for comparison.)

[0069] Coaxial wet spinning process

[0070] Through vertical coaxial extrusion spinning, a biaxial wet spinning needle with an inner diameter of 22G (0.41mm) and an outer diameter of 17G (1.01mm) was used, and a 2%wt calcium chloride aqueous solution was prepared as a coagulation bath. The inside of the wet spinning needle was the prepared core layer conductive slurry, and the outside was the sheath layer spinning solution. The injection pump was used to extrude the inner layer at a speed of 10ml / h and the outer layer at a speed of 15ml / h.

[0071] like Figure 5 As shown in (a), LM is added to water and dispersed and micronized by a homogenizer. It can be observed that the LM particles clump and stick together, making it difficult to effectively achieve uniform dispersion. This is because after LM is dispersed in water in a micronized manner, an oxide layer will form on the surface. Although it has the effect of micronization, the thin oxide layer is unstable and prone to adhesion and dealloying. This results in an unstable and unevenly dispersed suspension of LM. LM is added to WPU and dispersed by a homogenizer to observe the existence characteristics of LM particles. It can be seen that by dispersing with WPU, uniform and stable LM particles can be obtained. At the same time, there will be no adhesion between the particles, and they can exist stably in the aqueous solution for a long time. Furthermore, the size of the LM dispersed particles is characterized by ultra-depth microscopy and scanning electron microscopy images, and the particle size diameter is about 30 microns.

[0072] The particle structure of LM dispersed in WPU aqueous solution is different from that of LM dispersed in deionized water. The inner layer is pure LM, which will quickly form an oxide layer (Ga2O3) when dispersed in aqueous solution. 3+ In order to prove the chelation effect between the carboxyl groups on the WPU molecular chain and the LM oxide layer, the pure WPU film and the film after drying the LM dispersed particles were analyzed by infrared spectrum. -1 The shift and broadband vibration of the CO peak on the nearby carboxyl group can effectively prove the chelation between the carboxyl group and the gallium ion, such as Figure 5 (d) as shown.

[0073] like Figure 5 As shown in (e), by analyzing the contact angles of pure LM and LM particles dispersed in WPU with polyurethane materials, it was found that the contact angle of pure LM droplets with polyurethane film was 118.48°, and after stretching by 50%, the contact angle was 89.65°. However, the contact angle of LM droplets dispersed in WPU with polyurethane film was only 56.25°, and after stretching by 50%, the contact angle was only about 5°. This is due to the adhesion and affinity of the WPU layer, which enables the droplets to move well with the stretching of the polyurethane film.

[0074] like Figure 5As shown in (f), the injection extrusion routes of pure LM, LM dispersed in water, and LM dispersed in WPU are simulated respectively. Comparison of the extrusion effects of LM in three different systems. Due to the high surface tension of LM, pure LM is in the form of microinjection. When extruded, it is in the form of droplets, forming an intermittent LM path, and it is difficult to form a continuous path. When LM is dispersed using water as a solvent, a thin oxide layer is easily formed on the surface, which can effectively disperse LM into microparticles. However, its oxide layer is thin and extremely unstable, which causes adhesion between particles and uneven distribution. From the simulation of the spinning path, it can be seen that due to its uneven adhesion distribution, the microinjection extrusion is discontinuous, showing an intermittent LM path, and it is difficult to achieve effective continuous spinning. When LM is dispersed in WPU, the WPU thin layer makes LM stably and evenly dispersed in the dispersion system with water as the solvent. From the spinning extrusion path, it can be seen that the WPU dispersion system of LM can obtain a continuous and uniform spinning path through microinjection extrusion, achieving the effect of continuous spinning.

[0075] like Figure 6 As shown, the SEM image of the fiber surface shows a smooth fiber surface, and the polyurethane-SA composite cortical elastomer material provides a smooth surface for the fiber. The diameter of the fiber is about 600-800μm. From the SEM image of the cross section, it can be seen that the fiber prepared by coaxial wet spinning can obtain an obvious core-sheath structure, with the inner layer being LM particles and the outer layer being a protective layer of polyurethane. Further, through the element mapping of the cross section, the distribution of carbon (C), calcium (Ca), gallium (Ga), and indium (In) elements in the core-sheath structure were detected respectively. It can be found that the carbon element is mainly concentrated in the cortex, which is because the carbon element is mainly in the cortex of polyurethane. The calcium element is not only distributed in the cortex, but also in the core layer. This shows that since the outer layer of the LM particles is a WPU layer, it also has the ability to adsorb calcium ions, so that the element is distributed inside the fiber. The gallium and indium elements are mainly concentrated in the core layer of the fiber, indicating that LM is concentrated in the core layer of the fiber.

[0076] Since elastic conductive fibers are mostly used to integrate flexible wearable electronic products through knitting or weaving, the elastic conductive fibers need to have a suitable size and good flexibility. Since the spinning process uses a micron-sized spinning needle, micron-sized elastomeric fibers can be obtained. The prepared elastic conductive fibers have a diameter similar to that of copper wire. The difference is that since the fibers are prepared based on polyurethane materials, the prepared elastic conductive fibers have better flexibility than copper wires and can be easily knotted and folded. Conductive fibers of this size can easily pass through the needle. These characteristics make the prepared elastic conductive fibers have good knitting and weaving properties.

[0077] Study on Fiber Conductive Activation

[0078] LM fills the core structure of the fiber in the form of dispersed particles. At the same time, the oxide layer of the LM particles and the coating of the WPU layer make the particles stably exist in the fiber core layer. The prepared elastic conductive fiber needs to activate the conductive pathway to achieve conductivity. When not activated, LM is stably dispersed in the fiber core layer in the form of particles. During the fiber stretching process, the fiber is collected and the cross-sectional area becomes smaller, thereby squeezing the internal LM particles, so that the LM inside the fiber will form an LM pathway from the particle form. As the outer layer WPU and the oxide layer are further destroyed, the fiber core layer LM forms a complete connection pathway, thereby achieving the conductivity of the core-sheath conductive fiber. Figure 7 (a) shows the detection of fiber resistance change. As the fiber tensile deformation increases, the fiber resistance changes from infinity, megaohm level to less than ten ohms, indicating that the fiber conductive circuit is conductive.

[0079] Fiber conductivity

[0080] Since the resistance of the fiber changes over a wide range when it is initially stretched, a unified conductivity activation method needs to be established when testing the conductivity. Therefore, the conductivity calculation method of the present invention is based on calculating the conductivity of the fiber according to the resistance of the fiber after the fiber is stretched 100%. This is because after the fiber is stretched 100%, the resistance value changes tend to be stable and can recover almost 100%. At the same time, when the fiber is stretched to 100%, the connection path formed by the fiber core layer LM can be visually observed through a microscope. Figure 7 As shown in (b), a 4 cm long conductive fiber was stretched 100% and then recovered. The resistance was measured by a multimeter to be 2.485Ω. The conductivity of the fiber was calculated to be 1.28×10 5 S / m, while the conductivity of LM itself is 3.4×10 6 S / m.

[0081] Fiber mechanical properties

[0082] like Figure 7 (c) shows the tensile cycle increment and tensile fracture curve of LM / WPU elastic composite conductive fiber. The prepared conductive fiber has a tensile strength of 17.2MPa and a fracture elongation of 558%, indicating that the conductive fiber with polyurethane as the sheath material has excellent mechanical properties.

[0083] Changes in fiber resistance under high deformation

[0084] like Figure 7(d) shows the change in resistance of the elastic conductive fiber after stretching activation. The resistance change rate under 200% strain is only 1.17%, and the resistance change rate is still less than 100% when the stretch breaks, that is, 558% strain. Therefore, the elastic conductive fiber shows a stable resistance change under large stretching. During the entire single stretching process, the resistance change rate of the fiber will first decrease and then increase, which is mainly due to the conductive activation method adopted to stretch the fiber to 100% activation. Therefore, during the initial stretching, the unactivated dispersed LM particles inside will be further activated, increasing the LM conduction path, and achieving "more conduction" of the LM path. Of course, this change is extremely subtle, and it can also reflect the sensitivity of the fiber to strain. As the stretching increases, the resistance change rate will increase. This is mainly because as the fiber length increases and the cross-sectional area decreases after stretching, the conductive path of its core layer will also be elongated, and the internal conductive path will also be hindered, resulting in reduced conductivity.

[0085] In order to characterize the resistance stability of elastic conductive fibers under multiple stretching, Figure 7 (e) is a graph showing the resistance change rate of the elastic conductive fiber after 100 cycles of stretching at 200% strain. The resistance change rate of the elastic conductive fiber shows a relatively stable change. However, it can still be observed from the figure that the resistance change rate of the elastic conductive fiber will slowly increase after multiple cycles of stretching. This is because after the elastic conductive fiber is stretched cyclically, especially after multiple stretching, the fiber cannot achieve a complete 100% recovery in a short time. Therefore, as the number of stretching cycles increases, the resistance change rate of the fiber will increase. In addition to large deformation due to stretching, bending is also one of the forms of large deformation of the fiber. Therefore, the change in resistance change rate of the elastic conductive fiber when bent was also tested and characterized. Fix the two ends and use the compression mode of the universal testing machine to simulate the bending of the elastic conductive fiber. Figure 7 (f) is the relationship curve of resistance change rate under different bending degrees. As the bending degree increases, the resistance change rate of the fiber will increase. However, this resistance change is still within a small range. It can be seen that when the bending is 85%, the resistance change rate is only 3%. Therefore, under large bending deformation, the fiber will also show stable and sensitive resistance changes.

[0086] The coaxial wet spinning process of this embodiment is through vertical extrusion spinning, which can not only maintain the core-sheath structure of the fiber well, but also can realize the unpowered drafting of the extruded fiber based on gravity due to the high density of the internal conductive slurry. If the coaxial wet spinning of this embodiment is coaxially extruded in the horizontal direction, the core layer LM will be lower than the bottom of the fiber due to the density difference of the core-sheath layer, making it difficult to construct the core-sheath structure.

Claims

1. A method for preparing a waterborne polyurethane fiber, comprising: (1) Aqueous polyurethane solution and sodium alginate SA are stirred and mixed, and degassed to obtain a spinning solution A; The waterborne polyurethane is a carboxylic acid type waterborne polyurethane; (2) mixing an aqueous polyurethane solution and a liquid metal LM, homogenously dispersing the mixture, standing the mixture, and removing the supernatant to obtain a slurry; wherein the liquid metal LM is a gallium-indium alloy or a gallium-indium-tin alloy; (3) The spinning solution A in step (1) is used as the sheath spinning solution, and the LM slurry in step (2) is used as the core slurry, and fibers are obtained by coaxial wet spinning.

2. The preparation method according to claim 1, characterized in that: The solid content of the aqueous polyurethane solution in step (1) is 5%-50%; the sodium alginate SA is 0.5%-3% of the mass fraction of the aqueous polyurethane.

3. The preparation method according to claim 1, characterized in that: The solid content of the aqueous polyurethane solution in step (2) is 5%-50%; the mass ratio of the aqueous polyurethane to the liquid metal LM is 10:1-1:

10.

4. The preparation method according to claim 1, characterized in that: The homogenization and dispersion in step (2) is 2000-20000 r / min; and the standing time is 3-10 min.

5. The preparation method according to claim 1, characterized in that: In the step (3), the outer layer spinning speed of the coaxial wet spinning is 2-200 ml / h, the inner layer spinning speed is 1-200 ml / h, and the coagulation bath is a 1-10%wt calcium chloride solution.

6. A waterborne polyurethane fiber prepared by the method of claim 1.

7. Use of the waterborne polyurethane fiber according to claim 6 in electronic devices.

Citation Information

Patent Citations

  • Preparation method for stretching-resistant spandex fibers for heavy crepes

    CN108060469A